Galectin 2 (gal-2) expression is downregulated on protein and mRNA level in placentas of preeclamptic (PE) patients. Issue 4 (April 2015) - Hutter, S.; Martin, N.; von Schönfeldt, V.; Messner, J.; Kuhn, C.; Hofmann, S.; Andergassen, U.; Knabl, J.; Jeschke, U.
Abstract Introduction Galectin 2 (gal-2) belongs to the proto type group and consists of two homologous carbohydrate recognition domains (CRDs) resulting in multiple sugar binding sites. The expression of gal-2 has been shown to be involved in processes of angiogenesis and inflammation but was not analyzed before in preeclamptic (PE) placentas. Therefore the aim of this study was an analysis of expression and localization of gal-2 in placentas from patients suffering from PE. Methods Placental tissues were obtained from 14 women following a normal course of pregnancy and 13 women with PE. Expression of gal-2 was evaluated with immunohistochemistry and a semi quantitative score. Gal-2 mRNA expression was quantified in placental tissue using real time TaqMan PCR. Identification of gal-2 expressing cells in the decidua was achieved by double immunofluorescence microscopy. Results Expression of gal-2 is downregulated in the syncytiotrophoblast of preeclamptic placentas. Downregulation of gal-2 could also be identified in the decidua of PE patients. These findings on protein level could be supported by the results of TaqMan PCR. Gal-2 is downregulated in PE placentas on mRNA level. Finally, gal-2 expressing cells could be identified as extravillous trophoblast cells in both normal pregnancy and PE. Discussion Gal-2 was identified as an inhibitor of arteriogenesis in a murine model supposedly via modulation of the monocyte/macrophage population. In PE, both the formation of spiral arteries as well as influx of macrophages are dramatically changed. Therefore we might speculate that disturbed transformation of spiral arteries in PE might correlate with the downregulated gal-2 expression by the trophoblast.